2023
DOI: 10.1038/s41598-022-27220-9
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic influence on extremes and risk hotspots

Abstract: Study of the frequency and magnitude of climate extremes as the world warms is of utmost importance, especially separating the influence of natural and anthropogenic forcing factors. Record-breaking temperature and precipitation events have been studied using event-attribution techniques. Here, we provide spatial and temporal observation-based analyses of the role of natural and anthropogenic factors, using state-of-the-art time series methods. We show that the risk from extreme temperature and rainfall events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…In particular, regional persistent rainstorm events often have multiple sources of water vapour that are closely related to the altitude layer, atmospheric circulation and complex interactions between various monsoon systems (Ding et al, 2020; Wang et al, 2021). Moreover, human activities also play an important role in the change in rainstorms (Estrada et al, 2023; Kong et al, 2017; Min et al, 2011). Especially for severe convective rainstorms, it can be found that the total explanation rate of large‐scale circulation factors is only about 50%.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, regional persistent rainstorm events often have multiple sources of water vapour that are closely related to the altitude layer, atmospheric circulation and complex interactions between various monsoon systems (Ding et al, 2020; Wang et al, 2021). Moreover, human activities also play an important role in the change in rainstorms (Estrada et al, 2023; Kong et al, 2017; Min et al, 2011). Especially for severe convective rainstorms, it can be found that the total explanation rate of large‐scale circulation factors is only about 50%.…”
Section: Discussionmentioning
confidence: 99%
“…This change observed in the indices of tropical night numbers in the Mediterranean region can be attributed to anthropogenic warming. In most land regions, including Europe and the Middle East, the probability of extreme temperatures at least doubled, with an increase of about 2 W·m −2 by 2018 in anthropogenic forcing (Estrada et al, 2023). Increasing tropical nights is consistent with night‐time low temperatures increasing about twice as rapidly as daytime highs over northern hemisphere mid‐latitudes in response to anthropogenic forcing (Donat & Alexander, 2012; Dwyer et al, 2012).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Such modifications can be produced by changes in the mean (i.e., existence of trends) and/or variability, as well as in the persistence of some variables of the climate system, or a combination of them. While the first two have received significant attention, 13–15 studies about the effects of changes in persistence on the probabilities of occurrence of extremes are much scarcer 16–18 . However, recent events with seemingly larger than usual duration, magnitude, and frequency 19 have invigorated research efforts for better understanding of the influence and nature of trends, changes in variability, and persistence over extremes 15,18,20–25 .…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] However, recent events with seemingly larger than usual duration, magnitude, and frequency 19 have invigorated research efforts for better understanding of the influence and nature of trends, changes in variability, and persistence over extremes. 15,18,[20][21][22][23][24][25] However, to obtain an adequate estimation of persistence, it is crucial to properly account for trends and noise. As discussed in the time-series literature, not accounting for trends or structural changes can bias persistence estimates upward, while the presence of noise imparts a downward bias.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation